Intelectuais, padrões de cientificidade e a escola como objeto de estudo: o lugar da produção e a produção do lugar em Luiz Pereira - Ribeiro, Núbia Ferreira (2007)
This research discusses the Luiz Pereira s work as social scientist. He played a special role defining school as sociologial issue. From 1950 to the years of dictatorship the political and academic scenery was occupied by intense debates about economic development. Brazilian politicians and intellectuals struggled to define the shape of our development and trough this process sociologists boasted a new political prominence due to the fact they were considered able to offer answers for increasing social problems. The more Brazil s social fabric became complex, the more sociological expertise was supposed to solve problems, identifying paths to a new world. This fact shows one peculiar situation because at the same time an enlarged contingency of workers found no place for everybody to work. Thus to write about development in that context meant struggle to conect sociology with socialism or capitalism. This upturn brought to arena of debates the Luiz Pereira s work. His work dedicated special attention to school in metropolitan places. Being a Florestan Fernandes s follower he build his own academic place. Firstly he considered schools as a very important sociological matter, thereafter he joined his previous studies on education with marxist repertoire, achieving, as a consequence, a prolific work that, in the end, made his research worthy to be considered fundamental for our current studies on development, work and education